The visualization handbook - Hansen, Charles D.; Johnson, Chris R. (Amsterdam ; Boston : Elsevier-Butterworth Heinemann, 2005)
The Visualization Handbook provides an overview of the field of visualization by presenting the basic concepts, providing a snapshot of current visualization software systems, and examining research topics that are advancing the field. This text is intended for a broad audience, including not only the visualization expert seeking advanced methods to solve a particular problem, but also the novice looking for general background information on visualization topics. The largest collection of state-of-the-art visualization research yet gathered in a single volume, this book includes articles by a whos who of international scientific visualization researchers covering every aspect of the discipline, including: Virtual environments for visualization Basic visualization algorithms Large-scale data visualization Scalar data isosurface methods Visualization software and frameworks Scalar data volume rendering Perceptual issues in visualization Various application topics, including information visualization. * Edited by two of the best known people in the world on the subject; chapter authors are authoritative experts in their own fields; * Covers a wide range of topics, in 47 chapters, representing the state-of-the-art of scientific visualization.
Part I. Introduction -- Part II. Scalar field visualization: isosurfaces -- Part III. Scalar field visualization: volume rendering -- Part IV. Vector field visualization -- Part V. Tensor field visualization -- Part VI. Geometric modeling for visualization -- Part VII. Virtual environments for visualization -- Part VIII. Large-scale data visualization -- Part IX. Visualization software and frameworks -- Part X. Perceptual issues in visualization -- Part XI. Selected topics and applications.
Includes bibliographical references and index.
Keywords: Information visualization; Computer graphics; Electronic books